Ultrasonic agglomeration applied to Durvillea Antarctica and Arthrospira platensis flours: Effects on thermophysical properties, protein conformational changes and microstructure - Osorio-Lira, F; Rivera-Tobar, D (ELSEVIER SCI LTD, 2025)
The effects of ultrasonic agglomeration (UA) on the thermophysical and structural properties of matrices based on flours from Durvillaea antarctica and Arthrospira platensis were evaluated. UA was applied under power amplitudes, times, and cycles, optimizing the processing conditions in the agglomerated matrix. The elastic modulus increased significantly under optimal UA conditions, reaching 43.08 +/- 1.93 N/m(2) at 90 % power amplitude, compared to 0.051 +/- 0.10 N/m(2) at 70 % power amplitude. Fractrutability increased by more than 50 %, reaching values up to 931.89 +/- 23.78 N (90 % power amplitude, 25 s, 3 cycles). The protein denaturation temperature increased to 134-139 degrees C with UA, indicating increased thermal stability. FTIR analysis revealed a reduction in beta-sheet content (from 70.9 +/- 3.1 % to similar to 50-58 %) and an increase in alpha-helix structures, reflecting protein unfolding. UA is an alternative to be explored in the food industry, with potential application in the development of functional and sustainable foods.